Cadmium dominance in heavy metal pollution: ecological risks and human health implications in the Guan River Estuary, China - Xu, Wenjian; Meng, Kun; Du, Wen; Cai, Zican; Li, Yanxia; Chen, Xiang; Zhang, Yimin (Frontiers in Marine Science, 2025)
Estuarine ecosystems are vulnerable to anthropogenic heavy metal pollution. This study examines cadmium (Cd) dominance in pollution and its ecological/human health impacts in China's Guanhe Estuary, a region heavily influenced by land-based inputs. Concentrations of six heavy metals (Cu, Pb, Zn, Cd, Cr, As) were measured in sediments and muscle tissues of 12 marine species across 11 sampling sites using atomic absorption and fluorescence spectrometry. Ecological risks were evaluated via pollution load index (PLI), geo-accumulation index (Igeo), and potential ecological risk index (ERI). Health risks were assessed using target hazard quotient (THQ) and hazard index (HI). The results showed that the sediment concentrations of Cu, Pb, Zn, Cd, Cr, and As were 16.75±2.25, 8.39±0.91, 55.15±5.18, 0.10±0.01, 64.64±3.22, and 11.92±0.99 mg/kg, respectively. PLI and ERI indicated moderate pollution and low ecological risk, and Cd emerged as the primary pollutant and risk to ecology, based on its high Igeo and Er indices. Bioaccumulation analysis revealed that marine invertebrates, such as crabs, shrimps, and edible molluscs, accumulated higher concentrations of heavy metals, particularly Cd, compared to fish. Health risk assessments indicated no significant non-carcinogenic risks to local residents (THQ/HI < 1) for most metal species. Cd dominates due to human activities like agricultural/industrial runoff and high bioavailability in fine sediments. Despite low health risks, Cd hotspots near Liezikou Estuary and the double jetty need stricter controls and monitoring. These findings highlight Cd as a key contaminant, informing global estuary cleanup efforts.